A comparative evaluation of the effect of addition of 8 mg dexamethasone to 2% lignocaine with adrenaline in mandibular third molar surgery: a split mouth randomised double blind study - Poorna, P.; Shetty, Premalatha; Kalyani, Veerbhadra; Shetty, Sameep; Upadya, Madhusudan; Mithra, Prasanna (Frontiers in Oral Health, 2024)
Background Impacted lower third molar surgeries involve trauma in a highly vascularized zone with loose connective tissue leading to inflammatory sequelae including postoperative pain, swelling, trismus and generalised oral dysfunction during the post-operative phase. In minor oral surgical procedures, an all-inclusive method to protract anaesthesia and reduce the inevitable post-operative sequelae is yet to be explored substantially. Aim To evaluate the efficacy of dexamethasone added to local anaesthetics in extending the depth and duration of anaesthesia and decreasing the postoperative complications after surgical removal of impacted third molars. Methodology A controlled, randomized, split-mouth, double-blind prospective study involving lower third molar surgery was performed in 35 patients wherein the test group (Group I) received 8 mg dexamethasone added to 2 ml of 2% lignocaine with epinephrine and the control group (Group II) received 2 ml of sterile water added to 2 ml of 2% lignocaine with epinephrine. Onset and duration of anaesthesia were evaluated; followed by evaluation of pain, swelling and trismus for 7 days post-surgery, using independent t-test and ANOVA for repeated measures. Results Test group had a faster onset of anaesthesia by 69 s and a lengthier duration of 128.4 min (p < 0.001). Pain scores (Visual Analogue Scale) in the first 24 h were 4.9 and 7.5 in the test and control group respectively (p < 0.001). The average dosing of analgesics until postoperative day 7 in the test and control group were 12.6 and 18.4 respectively (p < 0.001). The swelling was significantly lesser in the test group, in addition, trismus was significantly lesser by 1 cm on postoperative days 1 and 2 and 0.2 cm on day 7. Conclusion The addition of dexamethasone to lignocaine in the nerve block reduces the time of onset and significantly prolongs the duration of anaesthesia with decreased pain, swelling and trismus. Steroids mixed directly with the local anaesthetic agent can minimise the post-operative sequelae associated with third molar surgery with a single needle prick.